Does Low Protein Concentration of Tissue-type Plasminogen Activator Predict a Low Risk of Spontaneous Deep Vein Thrombosis? - Gram, Jørgen; Sidelmann, Johannes; Jespersen, Jørgen (Thrombosis and Haemostasis, 1995)
Many reports have demonstrated an abnormal fibrinolysis in a subset of patients with deep vein thrombosis. We have studied systemic global fibrinolytic activity and protein concentrations of tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor type 1 (PAI-1) in plasma of 25 young patients with a previous instance of spontaneous deep vein thrombosis documented by phlebography and in 50 healthy controls. The two populations were comparable with respect to a number of base-line variables (age, height, weight, etc.), while the patients had significantly lower fibrinolytic activity (p <0.02), and significantly higher protein concentrations of t-PA (p <0.0001) and PAI-1 (p <0.0006).We used probit scale plots to identify the consequence of different cut-off points to separate patients from controls. Reasonable separation could be obtained for t-PA with a cut-off point of 5.2 ng/ml and for PAI-1 18 ng/ml. The sensitivity and specificity for these cut-off points were for t-PA 73% (95% confidence interval 63%-84%) and for PAI-1 67% (confidence interval 55%-77%). The negative predictive value with a cut-off point t-PA concentration of 5.2 ng/ml was 85% (95% confidence interval 70%-94%). We observed a significantly negative association between concentration of t-PA and fibrinolytic activity (rs = -0.47; p <0.005) and also between PAI-1 and fibrinolytic activity (rs = -0.78; p <0.005).We conclude that a young healthy population is characterized by low protein concentration of t-PA (and PAI-1) compared with young patients with a previous instance of spontaneous vein thrombosis, and we tentatively state that a low protein concentration of t-PA predicts a low risk of spontaneous deep vein thrombosis.